X-RAY EXAMINATION OF DOG FOR THE ESOPHAGUS DILATATION (CLINICAL CASE) - Lokes-Krupka, T. P.; Kanivets, N. S.; Karysheva, L. P.; Soboleva, O. D.; Obidnyi, Ya. R. (Scientific Progress & Innovations, 2021)
The article describes a clinical case of mega-esophagus in a domestic Pekingese dog aged 8 years, weighing 5 kg. The animal was examined according to the generally accepted scheme, namely collecting anamnesis, clinical study (thermometry, palpation, auscultation), X-ray of the esophagus. History: general depression, restlessness, anorexia, frequent swallowing, dyspnea, cough, hyper-salivation, intermittent vomiting after feeding or drinking. During the dog’s examination, general depression at the background of anxiety, increased respiratory rate (29 movements/min) and heart rate (135 beats/min) were found. The body temperature was within physiological fluctuations and made 38.3 °C; at esophageal palpation, pain was not detected. According to the results of clinical studies, the veterinary doctor did not diagnose the development of esophageal dilation. But it should be noted that the anamnesis data of the diseased dog indicated dysphagia that were the signs of the esophagus dilatation (mega-esophagus). The next step was X-ray examination of the esophagus (head, neck and chest) of the diseased dog. On the radiograph, the mega-esophagus was visualized as a long dilatation of the esophagus with a diameter of 26.79 mm, which was filled with both liquid and gases. Moreover, in the chest cavity, the focuses of pneumonic infiltration were revealed. The obtained data of X-ray examination of the diseased dog clearly visualize the dilatation of the esophagus (megaesophagus), which causes metabolic disorders. Normally the esophagus is actively involved in the flow of food from the mouth into the stomach. In this case, the food lump, which is impregnated with saliva and partially chewed, enters the esophagus, which begins to contract. The contractions of the latter take place in the presence of the muscular layer, but in the case of the esophagus pathology, in particular its dilatation, the wall of the esophagus is stretched and tense, so the muscles do not contract. The feed mass that enters the esophagus cannot move further, remains in it and begins to rot (because the secretory glands in the esophagus are absent). The formed toxins of putrefactive micro-flora intoxicate the dog’s body, cause inflammation of the esophagus, nose, bronchi and even lungs. The prognosis is cautious and often unfavorable. Thus, the examination of the Pekingese dog with the use of X-ray examination enabled to establish the final diagnosis – mega-esophagus.